SAINT BASIL THE GREAT, MASTER OF PHILANTHROPY - MUREȘAN, Radu Petre (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
The present study aims to highlight the concept of philanthropy in the writings of Saint Basil the Great, the manner in which it was materialized during the lifetime of the Great Cappadocian Father and its relevance for the mission of the Orthodox Church in the contemporary society. Man as a social being and philanthropy as a result of the communion in love, following the Trinitarian model, are the main themes of Saint Basil’s sermons. The study shows that the philanthropy-centered discourse of Saint Basil would not have any impact if it weren’t reinforced by the personal example, when he shared all the wealth inherited from his parents with the poor, and built a whole philanthropic complex on the outskirts of Caesarea. Regarding the importance of St. Basil's writings for the current life of the Church, the study points out that St. Basil was actively involved in the life of society and tried, with audacity and perseverance, to denounce and correct its inequalities. In so doing, he proved to be a leader of the Church whose spiritual, administrative, and moral authority was so great that it could no longer be ignored or challenged by the authority of the state.